Fishing characteristics and spatial distribution of blue swimming crab size (Portunus pelagicus) in the waters of Pati District, Central Java Province: Karakteristik Penangkapan dan Distribusi Spasial Ukuran Rajungan (Portunus pelagicus) di Perairan Kabupaten Pati, Provinsi Jawa Tengah - Akhmad Nurhijayat; Zairion; Luky Adrianto (Departement of Aquatic Resources Management, Faculty of Fisheries and Marine Sciences, IPB University, 2022)
The increasing Blue swimming crab/BSC fishing activity is a response to the high demand of the international market. One of the potential coastal waters for BSC capture fisheries is Pati Regency. However, biological information related to BSC resources is still limited in this area. Therefore, the purpose of this study is to analyze the characteristics of BSC fishing and the size structure of the caught BSC. The study was conducted from December 2020 to March 2021. The method of data collection is observation and interview with fishermen, while the analysis is carried out descriptively. The location of BSC fishing is divided into 3 zones. The characteristics of BSC fishing locations include those related to the distance from the coastline, technical aspects and types of fishing gear, as well as the operational system of capture. The distance from the coastline in zone 1 is about 1-2 miles, zone 2 is about 2-3 miles, and zone 3 is more than 3 miles. The types of fishing gear used in zone 1 are bottom gill net, zone 2 and zone 3 are trapnet. The operational system of capture in zone 1 and zone 2 is carried out with daily trips, while in zone 3 it is carried out with weekly trips (babang). The distribution of carapace width sizes in zone 1 ranges from 44.00-139.00 mm (average 104.80±11.00 mm), in zone 2 it ranges from 72.10-138.00 mm (average 107.90±12.30 mm), and in zone 3 it ranges from 101.40-177.60 mm (average 126.50±11.50 mm).